Female genital tuberculosis: Histopathological study - Sharma, Reetu; Sherpa, Palzum; KC, Shiva Raj (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To find out the occurrence of genital tuberculosis in submitted samples of female genital tract, histopathological changes and age distribution. Methods: A retrospective study of 300 cases of extrapulmonary tuberculosis out of which 11 are of female genital tract based on laboratory record which was done from 2011 to 2018 at Patan Academy of Health Science, Lalitpur, Nepal. Descriptive analysis performed using MS Excel and SPSS 16. Results: Out of 30,000 biopsies 300 cases were of extrapulmonary tuberculosis. Out of 300 extrapulmonary tuberculosis females affected were 61%; out of these female patients 3.6% (n=11) were of female genital system. Maximum numbers of the cases lie in the age group 30-39 years. Lymph nodes comprised of 58%, followed by Gastrointestinal and Skin in 10% each. Out of all female genital tuberculosis 27% was seen in endometrium while majority (73%) was seen in tubo-ovarian complex; all of them had epithelioid granuloma and 54% had caseous necrosis. Ziehl Neelson stain done for acid fast bacilli was positive in 2 cases (18%). Conclusions: The female genital TB constituted 0.04% of total biopsies with 3.6% samples of female patients of total extrapulmonary tuberculosis. The commonest sites affected by tuberculosis were seen to be fallopian tube, ovaries and endometrium. Histopathology with special stains remains the gold standard for diagnosing female genital tuberculosis in Nepal even though there is advanced diagnostic modalities like PCR, culture of tissue and/or fluid (menstrual/peritoneal). Keywords: caseous necrosis, epithelioid granuloma, female genital, tuberculosis